Constructing Masculinity in Women’s Retailers: An Analysis of the Effect of Gendered Market Segmentation on Consumer Behavior - Filice, Eric; Neiterman, Elena; Meyer, Samantha B. (Qualitative Sociology Review, 2019)
While gender-based differences in consumer behavior have been previously investigated within the context of gender-neutral or unisex retailers, men’s behavior in women’s retailers remains largely unexplored. Furthermore, most studies frame the retail environment as a passive platform through which essential gender differences yield setting-specific bifurcated behavior, and do not address the role the commercial establishment and men’s shopping habits play in gender identity formation and maintenance. To address this gap, we analyzed men’s behavior in women’s retailers using interactionist and social constructionist theories of sex/gender. Data were collected through non-participatory observation at a series of large, enclosed shopping malls in South-Western Ontario, Canada and analyzed thematically. We found that men tend to actively avoid women’s retailers or commercial spaces that connote femininity, while those who enter said spaces display passivity, aloofness, or reticence. We suggest the dominant cultural milieu that constitute hegemonic masculinity— disaffiliation with femininity, an accentuation of heterosexuality, and a prioritization of homosocial engagement—nform the dialectical relationship between individual and institutional gender practice that manifests through consumption.